Recent progress in the design of photocatalytic H2O2 synthesis system - Wen, Haobing; Huang, Sen; Meng, Xianguang; Xian, Xiaole; Zhao, Jingjing; Roy, Vellaisamy A. L. (Frontiers in Chemistry, 2022)
Photocatalytic synthesis of hydrogen peroxide under mild reaction conditions is a promising technology. This article will review the recent research progress in the design of photocatalytic H2O2 synthesis systems. A comprehensive discussion of the strategies that could solve two essential issues related to H2O2 synthesis. That is, how to improve the reaction kinetics of H2O2 formation via 2e− oxygen reduction reaction and inhibit the H2O2 decomposition through a variety of surface functionalization methods. The photocatalyst design and the reaction mechanism will be especially stressed in this work which will be concluded with an outlook to show the possible ways for synthesizing high-concentration H2O2 solution in the future.